Benign Pseudoglandular Mesothelial Cell Inclusions in Cervical Lymph Nodes of a Patient With Multiple Malignancies: Case Report and Review of Literature. Issue 6 (November 2020) - Stefanko, Daniel P.; Lin, Grace Y.; Orosco, Ryan K.; Vavinskaya, Vera
Abstract : Abstract: Mesothelial cell inclusions in cervical lymph nodes are of exceedingly rare occurrence and can be mistaken for metastatic adenocarcinoma. We report the case of a 27-year-old woman with a history of chronic myelogenous leukemia, diagnosed at age 5 years, and a recent diagnosis of alveolar soft part sarcoma of the left parotid gland. The patient underwent a left parotidectomy and neck dissection with intraoperative finding of abnormal lymph nodes in levels II to V. Histological examination revealed clusters of bland cells with pseudoglandular formation in 6 of 14 level IV/V lymph nodes. Immunological stains were consistent with mesothelial origin, and the diagnosis of benign mesothelial cell inclusions was made. Recognition of this entity in the evaluation of lymph nodes is important to prevent misdiagnosis of metastatic disease, particularly in a patient with multiple known malignancies.